Evaluasi Kualitas Website dan Peralatan yang Digunakan pada Rekrutmen Anggota Polri dalam Rangka Mewujudkan SDM Polri yang Unggul - Raslin, Harvin; Annisaa Yusuf; Taufik Iqbal Ramdhani (Jurnal Litbang Polri, 2025)
The National Police of the Republic of Indonesia (Polri) is an institution responsible for maintaining internal security. To ensure a conducive security environment, Polri requires skilled and professional personnel. Therefore, Polri conducts recruitment based on the principles of Clean, Transparent, Accountable, and Humanistic (BETAH) to acquire high-quality human resources aligned with organizational needs and the expectations of society, the nation, and the state. This study aims to evaluate the quality of the website and equipment used in Polri's recruitment process to support the development of qualified human resources. The research applies a mixed-method approach, combining quantitative and qualitative data collected through questionnaires, in-depth interviews, and observations. Data were gathered from 4,108 respondents across 11 sampled regional police departments (Polda). The website evaluation used the Webqual 4.0 method, encompassing dimensions of usability, information quality, and interaction quality (service). For recruitment equipment, calibration records and recalibration status were reviewed to ensure accuracy and functionality. The findings show that the website www.penerimaan.polri.go.id is of excellent quality, with an average score of 2.93 out of 3.00, though technical challenges such as access issues during peak hours, upload size limitations, and manual verification processes remain. Additionally, Rikkes equipment, physical tests, and the Computer-Assisted Test (CAT) were rated accurate with an average score of 2.98, despite some tools still being manual and facing issues with facilities, internet and electricity. To enhance efficiency and transparency, standardizing equipment, advancing technology, and professionalizing the selection process are essential.